2000
DOI: 10.1002/ir.10502
|View full text |Cite
|
Sign up to set email alerts
|

Aren't You Satisfied Yet? Women Faculty Members' Interpretations of Their Academic Work

Abstract: Arguing that the professional lives of women faculty are different from those of their male counterparts, the author reviews several autobiographical texts focused on female faculty satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 12 publications
(11 reference statements)
1
35
0
1
Order By: Relevance
“…Similarly, Grant, Kennelly, and Ward (2000) found that both men and women faculty in scientific disciplines experience conflicts between career and family life. In contrast, Ropers-Huilman (2000) found that, even though women faculty were given mixed messages about having children, they sought coherence among the various aspects of their lives and many "spoke of the ways they envisioned their family and work experiences as complementing each other" (p. 26). Finkel and Olswang (1996), in a survey of women faculty at a research university, found women perceiving that the time required by children poses a serious threat to tenure.…”
Section: Have Child Need Tenure: a Review Of Relevant Literaturementioning
confidence: 99%
“…Similarly, Grant, Kennelly, and Ward (2000) found that both men and women faculty in scientific disciplines experience conflicts between career and family life. In contrast, Ropers-Huilman (2000) found that, even though women faculty were given mixed messages about having children, they sought coherence among the various aspects of their lives and many "spoke of the ways they envisioned their family and work experiences as complementing each other" (p. 26). Finkel and Olswang (1996), in a survey of women faculty at a research university, found women perceiving that the time required by children poses a serious threat to tenure.…”
Section: Have Child Need Tenure: a Review Of Relevant Literaturementioning
confidence: 99%
“…The first question compares responses from biomedical research faculty on their self-identified mediators and triggers as described in this study's conceptual framework (Hagedorn, 2000). The second explores responses by length of employment and by gender to see if differences exist between biomedical research faculty (Bender & Heywood, 2006;Callister, 2006;Fox & Colatrella, 2006;Ropers-Huilman, 2000;Sabharwal & Elizabeth, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…For example, a female faculty member in an otherwise all-male department may report lower levels of satisfaction due to perceived pressures of additional responsibilities to represent their department in various capacities as the only female faculty member. The same holds true for faculty who may be the only person of color or representative of any number of underrepresented demographics (Laden & Hagedorn, 2000;Ropers-Huilman, 2000;Wolf-Wendel & Ward, 2014). That feeling of being the only person of a certain demographic can come with dissatisfaction independent of the work itself.…”
Section: Mediatorsmentioning
confidence: 94%
“…For, to be true to the nature of feminism, feminist scholarship must be rooted in activism and social change. Indeed, Ropers-Huilman (2000) found that engaging in scholarship for social change contributes to the success of feminist academics.…”
Section: Methodsmentioning
confidence: 99%